OPTIMALISASI PENGGUNAAN ENERGI LISTRIK DI SGU - DANIEL SEMBIRING; YENNY WIDIANTY (LPPM, 2013)
Distribution electric power planning very is needed, with a purpose to full fill technical criterion, reliability aspect and efficiency. It’s his Optimum do not an electrics installation system very determined by its planning system, so that energy which is in supply really used as according to allotment, pursuant to burden assumption in this time and to come. Energy attached / PLN suplay is energy to be paid per kWh beside the expense of burden, where fixed burden paid is is same, though out of condition electricity entirely. SGU use electrics as source of especial energy. Existence of increase of Elementary Tariff of Electrics ( TDL), causing company require to be optimal of usage of its electrics energy, on the chance of can degrade expense which must in paying to the order of PLN party/ side. SGU (SWISS German University) is a university residing in Komplek Edu Town BSD, Serpong-Tangerang. Institution Swiss Germany University-Asia), founded in the year 2000, is effort with among/between Germany, Austrian, Swiss and Indonesia. If we can say as a industry, hence we will categorize this as a service industries. As us know with, input from a service industries specially SGU, that is grad student from SMA, or on an equal. Along existing activity, that is [at] activity process learn and teach, which using many electrics energy, expense of which in releasing very big, in seeing from expense which must in paying SGU party/ side to PT. PLN. Trouble-Shooting taken is with Pareto diagram, histogram and matter done/conducted for the minimization of the expense of usage of electrics energy, is to do/conduct some change of operational system and procedure operational standard from existing equipment Keywords: Optimation, electrics energy, white colars